Aerobic capacity is a key factor in maintaining maximum skating speed in elite hockey players - Andrich, D. E.; St-Pierre, D. H.; Comtois, A. S. (Applied Physiology, Nutrition, and Metabolism, 2012)
Ice hockey players rely mostly on anaerobic power to perform short, intense actions. On the other hand, aerobic power seems to play an important role in hockey performance, even if some studies haveshown both determinants to be poorly correlated. In fact, therecould be a minimal V. O2max above which hockey performances arenot ameliorated. The purpose of this study was to measure the effect of aerobic capacity on maintaining mid-duration maximum skating speed. A total of 96 elite hockey players participated in this study.They were first asked to perform an on-ice test to measure maximal aerobic capacity. The test consisted in an incremental 60-s skate: 30-s rest multi-stage shuttle test in which the players would skate back and forth to the sound of an audio signal over 45 m until maximum speed was reached. The V. O2max was measured using a portable metaboliccart and results were expressed in ml/kg/min. Following 2 days of rest, each player performed the anaerobic test. They skated at maximum speed at a distance of 20 m for 12 times, with each back and forth distance timed as a lap, for a total of 6 laps. One-way ANOVA was used to assess the differences between 3 groups, which were classified as: V. O2max = 52, V.O2max = 52-58 and V.O2max = 58. We found no difference in times between groups for shuttle laps 1 and 2. However, from lap 3 to 6, the V. O2max = 58 group had significantly faster times than the V. O2max = 52 group. Thus, players with higher maximal aerobic capacity are able to maintain a faster pace throughout maximal anaerobic effort. From these results, it seems that sustained anaerobic power is dependant on maximal aerobic capacity.